Incubators, Accelerators and Regional Economic Development - Margarida Madaleno; Max Nathan; Henry Overman; Sevrin Waights (Institute of Labor Economics (IZA), 2018)
A growing wave of co-location programmes promises to boost growth for entrepreneurs and young firms. Despite great public and policy interest we have little idea whether such programmes are effective. This paper categorises accelerators and incubators within a larger family of co-location interventions. We then develop a single framework to theorise workspace-level impacts. We summarise available evaluation evidence and sketch implications for regional economic policy. We find clear evidence programmes are effective overall. But we know little about how effects operate – or who benefits. Providers and policymakers should experiment further to establish optimal designs.
Keywords: L26; O32; R30; R58; 330; entrepreneurship; incubators; accelerators; clusters; cities; economic development